The Interplay of Mycosporine-like Amino Acids between Phytoplankton Groups and Northern Krill (Thysanoessa sp.) in a High-Latitude Fjord (Kongsfjorden, Svalbard) - Bo Kyung Kim; Mi-Ok Park; Jun-Oh Min; Sung-Ho Kang; Kyung-Hoon Shin; Eun Jin Yang; Sun-Yong Ha (Marine Drugs, 2022)
We investigated pigment and mycosporine-like amino acid (MAA) concentrations of phytoplankton and Northern krill (Thysanoessa sp.) in sub-Arctic Kongsfjorden. Chlorophyll a (Chl-a) concentrations in the surface and middle-layer water were 0.44 μg L−1 (±0.17 μg L−1) and 0.63 μg L−1 (±0.25 μg L−1), respectively. Alloxanthin (Allo, a marker of cryptophytes) was observed at all stations, and its mean values for surface and middle-layer water were 0.09 μg L−1 (±0.05 μg L−1) and 0.05 (±0.02 μg L−1), respectively. The mean MAA-to-Chl-a ratios at the surface (3.31 ± 2.58 μg (μg Chl-a)−1) were significantly higher than those in the middle-layer water (0.88 ± 0.49 μg (μg Chl-a)−1), suggesting that these compounds play an important role in reducing UV photodamage. In gut pigment levels of Northern krill, the most abundant accessory pigment was Allo (2.79 ± 0.33 μg g−1 dry weight; d.w.), as was the accumulation of Chl-a (8.29 ± 1.13 μg g−1 d.w.). The average concentration of MAAs was 1.87 mg g−1 d.w. (±0.88 mg g−1 d.w.) in krill eyes, which was higher than that in all other body parts (0.99 ± 0.41 mg g−1 d.w.), except for the gut. Thysanoessa sp. was found to contain five identified MAAs (shinorine, palythine, porphyra-334, mycosporine-glycine, and M-332) in the krill eye, whereas shinorine and porphyra-334 were only observed in the krill body, not the eyes and gut. These findings suggest that Northern krill accumulate MAAs of various compositions through the diet (mainly cryptophytes) and translocate them among their body parts as an adaptation for photoprotection and physiological demands.